Metastable perovskite Bi1-xLaxFe0.5Sc0.5O3 phases in the range of the compositional crossover. (2nd September 2017) - Salak, A. N.; Khalyavin, D. D.; Zamaraite, I.; Stanulis, A.; Kareiva, A.; Shilin, A. D.; Rubanik, V. V.; Radyush, Yu. V.; Pushkarev, A. V.; Olekhnovich, N. M.; Starykevich, M.; Grigalaitis, R.; et al.
ABSTRACT: Perovskite ceramics of the Bi1- x La x Fe0.5 Sc0.5 O3 composition (0.30 ≤ x ≤ 0.35) that cannot be sintered in bulk form as a single phase using the conventional ceramic route were successfully prepared using the high-pressure/high-temperature technique. It has been shown that the room-temperature compositional crossover from the antipolar phase whose incommensurate modulation of displacements of Bi/La and oxygen is described by the Imma (00γ)s00 superspace group to the non-polar Pnma phase occurs in the narrow range between x = 0.33 and x = 0.34 with no phase coexistence. The features of this compositional crossover are discussed in comparison with that observed in the Bi1- x La x FeO3 system.